2010
DOI: 10.1007/s10792-009-9341-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the management of ocular snake-bite injuries

Abstract: Ocular snake-bite injuries are quite rare away from natural habitats. However, when exotic animals are kept in captivity, the injuries sustained and their management can pose challenges when they present to their local eye department. This report describes an atypical eye injury inflicted by a python and its successful management involving surgical, laser and medical interventions. The case highlights the possible pitfalls resulting from the unusual mechanism of injury and the steps to avoid them. The article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Another 5-year-old female patient suffered from snake venom injection directly to her eye, leading to eye enucleation due to sever ocular necrosis [ 47 ]. However, another victim was bitten by Python molurus (non-venomous) to his left eye, causing corneo-scleral laceration and hyphaema [ 48 ]. After appropriate treatments, including Argon laser retinopexy, he was discharged after one week.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Another 5-year-old female patient suffered from snake venom injection directly to her eye, leading to eye enucleation due to sever ocular necrosis [ 47 ]. However, another victim was bitten by Python molurus (non-venomous) to his left eye, causing corneo-scleral laceration and hyphaema [ 48 ]. After appropriate treatments, including Argon laser retinopexy, he was discharged after one week.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Standard of care for nonvenomous site bites elsewhere on the body does not include empiric antibiotics to prevent secondary infections after snakebites, although tetanus prophylaxis should be provided as needed. Of those with reported drug selections (five cases) [1][2][3][14][15], each patient received treatment with a topical fluoroquinolone, although the specific drug of choice varied. Kleinman et al discussed the likelihood of bacterial stomatitis, especially in captive snakes, as a reason for antibacterial therapy in ocular snakebite injuries and found that in the pet Boa constrictor case, cultures from the teeth of the snake showed multiple species of Gram-negative rods [3].…”
Section: Discussionmentioning
confidence: 99%
“…Other medications were also utilized. Three cases (50%) received a topical steroid [1,12,15], one case received subconjunctival antibiotics intraoperatively [2], and two cases (33%) received a topical cycloplegic [1,14]. Despite venomous snake bites to the eye having a poor visual prognosis, each of the nonvenomous cases ultimately ended with a bestcorrected visual acuity of better than 20/40.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of penetrating ocular injuries with direct intraocular injection of venom from a snakebite resulted in extensive intraocular hemorrhage and necrosis requiring either enucleation or evisceration . On the other hand, those who experienced penetrating ocular injuries from nonvenomous snakebites had uneventful vision recovery after surgical repair of the corneal or scleral defect …”
Section: Introductionmentioning
confidence: 99%
“…6,7 On the other hand, those who experienced penetrating ocular injuries from nonvenomous snakebites had uneventful vision recovery after surgical repair of the corneal or scleral defect. [8][9][10] In canine patients, despite the common occurrence of snakebite injuries to the face, ocular and periocular involvement is rarely reported. A retrospective review by Martin et al 11 described ophthalmic abnormalities secondary to nine periocular and two ocular snakebites in dogs.…”
Section: Introductionmentioning
confidence: 99%